Caloric density of aquatic macrophytes in different environments of the Baía river subsystem, upper Paraná river floodplain, Brazil - Lopes,Célia de Almeida (2006)
The aim of this work was to determine the caloric density of leaves, stems and roots of aquatic macrophytes in different environments of the Baía subsystem (Baía river and Fechada and Guaraná lagoons) on the Upper Paraná river floodplain, in addition to identify the variability between ecological groups. Samplings of Eichhornia crassipes, Salvinia spp, Pistia stratiotes, Eichhornia azurea, Polygonum sp, Cyperaceae and Poaceae were carried out in February 2003. Spatial differences in the caloric densities were not observed for these plants. Caloric density values varied from 1906.9 cal/g dry weight (root) to 4675.0 cal/g dry weight (leaf). However, significant differences between the caloric content averages of the vegetative structures were observed only for Polygonum sp and Salvinia spp. In relation to the ecological groups, the highest average value was verified for the emergent macrophytes (3529.7 ± 722.5), which were significantly different from the floating ones (3056.5 ± 571.0). There was no difference between the sites included in the subsystem when the caloric densities were compared.